O equilíbrio do ser e a permacultura - Pereira, Rafaela Kleinhans (2016)
Several problems of contemporary society are related with the economic, political and cultural systems besides worldview that throughout the history of humankind have become crises, sometimes unavoidable and other induced and even provided. Within this context is the environmental issues affecting the various forms of public health. In the 60 and 70 various problems related to the environmental impact by pollution and exploitation of natural resources have led many alternative culture movements in favor of the rescue of ethical and moral values that provide a healthier relationship with the natural environment. One of these movements is permaculture, called "permanent culture", permaculture is composed of a series of principles and foundations for the establishment of an ecological culture in order to provide sustainable human communities. In João Pessoa, in 2011 through a partnership between the Department of Health and Department of Environment the first training was held in permaculture opening 50 vacancies distributed among government officials, students and other interested parties, passing then to include permaculture Petal Health and Wellness in the care of public health through Integrative and Complementary Practices in Health (PIC). Concurrently with this process, the mobilization of therapists for the implementation of the National Policy Integrative and Complementary Practices in Health (PNPIC) resulted in the creation of service centers specialized in PICs, including the Balance of Being.Considered the biggest of the three experiences this center offer a variety of group and individual therapies such as tai chi, yoga, reflexology, massage therapy, art therapy, reiki, aromatherapy, acupuncture, auriculoacupuncture, biodance, community therapy and among others. A collective therapies offered by Cpics Balance of Being are the permaculture activities implemented through the initiative of the therapists of the Center and with the support of the General Coordination, these activities take place in an area that initially was planned to be used as parking lot in the inner space of Cpics Balance of Being. Therefore the central object of this study was ecological culture and specific objective was monitoring permaculture activities in Balance of Being seeking to understand the meaning and motivations of those involved in construction and development of Cpics - who attributed their actions when they decided to expropriate the initiative of innovative profile and assess to what extent the initiative and the Centers activities that promote the social capital of the agents involved in relation to health practices.